Alkali-free bioactive glasses for bone regeneration - Kapoor, Saurabh (2015)
Bioactive glasses and glass-ceramics are a class of third generation biomaterials which elicit a special response on their surface when in contact with biological fluids, leading to strong bonding to living tissues. The purpose of the present study was to develop diopside based alkali-free bioactive glasses in order to achieve good sintering behaviour, high bioactivity, and a dissolution/ degradation rates compatible with the target applications in bone regeneration and tissue engineering. Another aim was to understand the structure-property relationships in the investigated bioactive glasses. In this quest, various glass compositions within the Diopside (CaMgSi2O6) – Fluorapatite (Ca5(PO4)3F) – Tricalcium phosphate (3CaO•P2O5) system have been investigated. All the glasses were prepared by melt-quenching technique and characterized by a wide array of complementary characterization techniques. The glass-ceramics were produced by sintering of glass powders compacts followed by a suitable heat treatment to promote the nucleation and crystallization phenomena. Furthermore, selected parent glass compositions were doped with several functional ions and an attempt to understand their effects on the glass structure, sintering ability and on the in vitro bio-degradation and biomineralization behaviours of the glasses was made. The effects of the same variables on the devitrification (nucleation and crystallization) behaviour of glasses to form bioactive glass-ceramics were also investigated. Some of the glasses exhibited high bio-mineralization rates, expressed by the formation of a surface hydroxyapatite layer within 1–12 h of immersion in a simulated body fluid (SBF) solution. All the glasses showed relatively lower degradation rates in comparison to that of 45S5 Bioglass®. Some of the glasses showed very good in vitro behaviour and the glasses co-doped with zinc and strontium showed an in vitro dose dependent behaviour. The as-designed bioactive glasses and glass–ceramic materials are excellent candidates for applications in bone regeneration and for the fabrication of scaffolds for tissue engineering.